Adaptations to comprehensive abortion care during the COVID-19 pandemic: case studies of provision in Bolivia, Mali, Nepal, and the occupied Palestinian territory - Annik Mahalia Sorhaindo; Sarah Castle; Lola Flomen; Eva Lathrop; Shirine Mohagheghpour; Rasha Dabash; Francelle Kwankam Toedtli; Rebecca Wilkins; Laurence Läser; Patricia Titulaer; Ernest Nyamato; Mary Lea Dakouo; et al. (Sexual and Reproductive Health Matters, 2023)
The COVID-19 pandemic impacted comprehensive abortion care provision. To maintain access to services while keeping individuals safe from infection, many organisations adapted their programmes. We conducted a programme evaluation to examine service adaptations implemented in Bolivia, Mali, Nepal, and the occupied Palestinian territory. Our programme evaluation used a case study approach to explore four programme adaptations through 14 group and individual interviews among 16 service providers, facility managers and representatives from supporting organisations. Data collection took place between October 2021 and January 2022. We identified adaptations to comprehensive abortion care services in relation to provision, health information systems and counselling, and referrals. Four overarching strategies emerged: (1) the use of digital technologies, (2) home and community outreach, (3) health worker optimisation, and (4) further consideration of groups in vulnerable situations. In Bolivia, the use of a messaging application increased access to confidential gender-based violence support and comprehensive abortion care. In Mali, the adoption of digital approaches created timely and complete data reporting and trained members of the community served as “interlocutors” between the communities and providers. In Nepal, an interim law expanded medical abortion provision to pharmacies, and home visits complemented facility-based services. In the occupied Palestinian territory, the use of a hotline and social media expanded access to quick and reliable information, counselling, referrals, and post-abortion care. Adaptations to comprehensive abortion care service delivery to mitigate disruptions to services during the COVID-19 pandemic may continue to benefit service quality of care, access to care, routine monitoring, as well as inclusivity and communication in the longer term.